Ressentiment: reflections on mimetic desire and society - Tomelleri, Stefano (Breakthroughs in Mimetic Theory, 2015)
Intro -- Contents -- Foreword by René Girard -- Foreword by Paul Dumouchel -- Acknowledgments -- Introduction -- Chapter 1. The Revolt of the Slaves at the Masters' Banquet -- Chapter 2. Bourgeois Philanthropy -- Chapter 3. The Surprise Box of Ressentiment -- Chapter 4. The Last of the Scapegoats -- Chapter 5. The Mimetic Nature of Our Ressentiment -- Chapter 6. Toward a Sociology of Ressentiment -- Chapter 7. From Victim-Playing to the Ethics of Ressentiment -- Conclusion -- Notes -- Bibliography -- Index.